Anmeldelser - Tvarnø Lind, Tore (Danish Yearbook of Musicology, 2012)
Review of: Christian Troelsgård: Byzantine Neumes: A New Introduction to the Middle Byzantine Musical Notation Monumenta Musicae Byzantinae, Subsidia, 9. Copenhagen: Museum Tusculanum Press, 2011.